PERAN PEMIKIRAN FATIMA MERNISSI DALAM MEMAHAMI ISLAM DAN KEMODERNAN DI MAROKO - Taufik, Muhammad (TASHWIR, 2022)
Abstract: This article discusses Islam and modernity in a country in North Africa, Morocco. The research question is how is Islam and modernity in Morocco and their relationship to the fate of women in the perspective of Fatima Mernissi? From the results of this study, it was found that between Islam and modernity in Morocco is something that has not meet expectations. According to Mernissi, there is still marginalization of women in the socio-political and religious aspects of life in Morocco. Because it is related to the interpretation of religion, Mernissi said that there is a need for a hermeneutical and socio-historical approach that adapts to the context, Islam for her is always actual in its development, including in this modern era. What is new from this research is that Islam and modernity in Morocco have not gone hand in hand, although times have changed, they are still not in line. While the goal that the author wants to achieve in this paper is to complete the lack of studies that have ever existed about Mernissi's thinking whose emphasis is that modernity should be directly proportional to the fate of women who are equal to men.Keywords: Islam; Modernity; Morocco; Fatima Mernissi; Hermeneutik and Socio Historical Approach; Marginalization of Women Abstrak: Dalam artikel ini, kami menganalisis hubungan antara Islam dan modernitas di Maroko, sebuah negara di Afrika Utara, melalui lensa pemikiran Fatima Mernissi. Kami bertanya bagaimana Islam dan modernitas di Maroko dan hubungannya dengan nasib perempuan dilihat dari perspektif Mernissi. Melalui studi ini, kami menemukan bahwa hubungan antara Islam dan modernitas di Maroko belum sesuai dengan harapan. Menurut Mernissi, masih terdapat marginalisasi perempuan dalam aspek sosial-politik dan agama dalam kehidupan di Maroko. Karena ini terkait dengan interpretasi agama, Mernissi menyatakan bahwa diperlukan pendekatan hermeneutik dan sosio-historis yang sesuai dengan konteks. Menurutnya, Islam selalu relevan dalam perkembangannya, termasuk dalam era modern ini. Hasil baru dari penelitian ini adalah bahwa Islam dan modernitas di Maroko belum berjalan bersama-sama, meskipun zaman telah berubah, mereka masih tidak selaras. Tujuan dari penulis dalam artikel ini adalah untuk menyelesaikan kekurangan studi yang pernah ada tentang pemikiran Mernissi yang menekankan bahwa modernitas harus sebanding dengan nasib perempuan yang sama dengan laki-laki.Kata Kunci: Islam, Modernitas, Maroko, Fatima Mernissi, Pendekatan Hermeneutik dan Sosio-Historis, Marginalisasi Perempuan